EFFECTS OF COGNITIVE RESTRUCTURING ON ACADEMIC PROCRASTINATION AMONG SECONDARY SCHOOL STUDENTS IN JALINGO METROPOLIS, TARABA STATE, NIGERIA - Muhammad, Ahmad Baba; Inda, Abdulmumini; Bakari, Usman; Haruna, Rabiu; Saleh, Sofiazianti (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the effect of cognitive restructuring technique on academic procrastination among secondary school students in Jalingo metropolis. Three hypotheses were formulated and tested. The population of the study was 160, students from which 15 students were purposely selected. This study employed a quasi-experimental design which took the form of pre-test and post-test. The participants were exposed to treatment (cognitive restructuring technique). The instrument used for data collection was the Academic Procrastination Assessment Scale Revised (APS-R) designed by Abu-Ghazal. Data were analysed using paired sample t-test to test the null hypotheses. The findings revealed that cognitive restructuring techniques was effective in reducing academic procrastination cramming (P=0.001), distraction of attention (P=0.0003) and laziness (P=0.001) among secondary school students. Based on the findings, it was recommended that psychologists and counsellors should be encouraged to use cognitive restructuring in handling students with academic procrastination problems.